Low Serum Calcium and Magnesium Levels and Rupture of Intracranial Aneurysms. Issue 7 (July 2018) - Can, Anil; Rudy, Robert F.; Castro, Victor M.; Dligach, Dmitriy; Finan, Sean; Yu, Sheng; Gainer, Vivian; Shadick, Nancy A.; Savova, Guergana; Murphy, Shawn; Cai, Tianxi; Weiss, Scott T.; et al.
Abstract : Background and Purpose—: Both low serum calcium and magnesium levels have been associated with the extent of bleeding in patients with intracerebral hemorrhage, suggesting hypocalcemia- and hypomagnesemia-induced coagulopathy as a possible underlying mechanism. We hypothesized that serum albumin-corrected total calcium and magnesium levels are associated with ruptured intracranial aneurysms. Methods—: The medical records of 4701 patients, including 1201 prospective patients, diagnosed at the Brigham and Women's Hospital and Massachusetts General Hospital between 1990 and 2016 were reviewed and analyzed. One thousand two hundred seventy-five patients had available serum calcium, magnesium, and albumin values within 1 day of diagnosis. Individuals were divided into cases with ruptured aneurysms and controls with unruptured aneurysms. Univariable and multivariable logistic regression analyses were performed to determine the association between serum albumin-corrected total calcium and magnesium levels and ruptured aneurysms. Results—: In multivariable analysis, both albumin-corrected calcium (odds ratio, 0.33; 95% confidence interval, 0.27–0.40) and magnesium (odds ratio, 0.40; 95% confidence interval, 0.28–0.55) were significantly and inversely associated with ruptured intracranial aneurysms. Conclusions—: In this large case–control study, hypocalcemia and hypomagnesemia at diagnosis were significantly associated with ruptured aneurysms. Impaired hemostasis caused by hypocalcemia and hypomagnesemia may explain this association. Abstract : Supplemental Digital Content is available in the text.